IPhone : Portable Genius - McFedries, Paul (Portable genius., 2015)
This edition is packed with practical advice and covers all the key features in clear, no-nonsense language accessible to those new to the iPhone family or iOS 8. This full-color guide is designed for the visual learner, featuring plenty of screenshots that illustrate various techniques. Genius icons highlight smarter, more innovative ways to do what you need to do better and faster. You'll find essential information about iOS, Siri, iCloud, and learn how to use your iPhone to manage, organize, and navigate your life. You will learn how to connect to a network, configure your settings, and work with iCloud; max out the media features, surf the Web, and check your e-mail; manage your contacts, appointments, e-books, and libraries; sync your apps, photos, music, and more. --